Remodelling Communication: FROM WWII TO THE WWW - GARY GENOSKO (University of Toronto Press, 2013)
Models perfuse communication studies. The most famous models bear an overt theoretical affi liation; for example, the mathematical/ engineering/transmission model is based in information theory. Most models are categorized into currents of emphasis and innovation, such as those that develop our understanding of audiences of receivers. While there are dozens of mass communication models bearing upon communication processes involved in television, newspapers, radio, and similar mass media, they are not widely known, and the history of their development remains largely a concern for a small number of specialists. Only a few important and infl uential models are recognized by the names of their authors, such as ‘Shannon and Weaver.’ Very few models of communication travel seamlessly across the long and numerous branches of communication studies and beyond. But make no mistake, all such models share core components that are repeatedly recoded, redrawn, and augmented.1 The family resemblances are unmistakable. The very idea that models might become a matt er for refl ection across specialist divides is best seen today in the philosophy and sociology of science. The assembling of models from far and wide in communication studies for critical purposes extends the subject of modelling into communication. Models are not only of interest to philosophers of science and of communication, for linguists, too, have made the modelling of language a subject worthy of att ention. Linguists treat models as methodological issues because they are oft en not based on the result of research into the structure of language but rather imported from elsewhere. As Polish linguist Roscislav Pazukhin observed, the ‘modelling principle’ in linguistics is exogenous, that is, borrowed from the sciences (physics, mathematics, astronomy, etc.)